2018
DOI: 10.1080/13880209.2018.1446030
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial effects of 18 medicinal plants used by the Khyang tribe in Bangladesh

Abstract: Context: The resistance of bacteria to antibiotics is raising serious concern globally. Asian medicinal plants could improve the current treatment strategies for bacterial infections. The antibacterial properties of medicinal plants used by the Khyang tribe in Bangladesh have not been investigated.Objective: The present study examines the antibacterial properties of 18 medicinal plants used by the Khyang tribe in day-to-day practice against human pathogenic bacteria.Materials and methods: Leaves, bark, fruits,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 52 publications
2
29
0
4
Order By: Relevance
“…Among the species of this family, the species Mesosphaerum suaveolens (L.) Kuntze (Figure 1), known in Brazil as "bamburral" and "alfazema-brava," is popularly used in the treatment of diseases related to gastrointestinal and respiratory tract [12], so that we hypothesize that the species is abundant in phytochemical constituents, which present biological activity against strains of pathogenic microorganisms, such as bacteria. This hypothesis is supported by the pharmacological and biological activities of these species already evidenced in the literature, such as antioxidant activity [13], neuroprotective [14], gastro-protective [15], antitumor [16], antinociceptive [17], anti-inflammatory [18], antifungal [19], anti-bacterial [20], insecticide [21], larvicide [8], and allelopathic action [22].…”
Section: Introductionmentioning
confidence: 75%
“…Among the species of this family, the species Mesosphaerum suaveolens (L.) Kuntze (Figure 1), known in Brazil as "bamburral" and "alfazema-brava," is popularly used in the treatment of diseases related to gastrointestinal and respiratory tract [12], so that we hypothesize that the species is abundant in phytochemical constituents, which present biological activity against strains of pathogenic microorganisms, such as bacteria. This hypothesis is supported by the pharmacological and biological activities of these species already evidenced in the literature, such as antioxidant activity [13], neuroprotective [14], gastro-protective [15], antitumor [16], antinociceptive [17], anti-inflammatory [18], antifungal [19], anti-bacterial [20], insecticide [21], larvicide [8], and allelopathic action [22].…”
Section: Introductionmentioning
confidence: 75%
“…The preliminary phytochemical screening study revealed that the crude ethanol extract, petroleum-ether fraction and chloroform fraction of L. grandis were rich of some vital chemical groups like alkaloids, steroids, tannins, saponins, glycosides and gummy types plants secondary metabolites ( The demand for novel antimicrobial agents from natural sources is mounting day by day 24 . In order to find out the prospective antimicrobial principles, the plant L. grandis was subjected for preliminary antimicrobial screening by disc diffusion method.…”
Section: Resultsmentioning
confidence: 99%
“…On the examination of the bacteria count on the spleen organs obtained the same results among groups given thyme alone or groups that were only given antibiotics and groups that were given a combination of thyme and antibiotics were not found any bacteria. This is possible because the spleen is the organ of the Reticulo Endothelial System (RES) which functions to consume bacteria and multiply when infection occurs, process antigens, and stimulate plasma cells to make antibodies (15). In the spleen organ, the high number of macrophages allows macrophages to kill MRSA bacteria effectively through the bloodstream, so that MRSA bacteria do not develop much in the spleen.…”
Section: Discussionmentioning
confidence: 99%